2007
DOI: 10.3917/spub.072.0111
|View full text |Cite
|
Sign up to set email alerts
|

Description de la situation du pian dans le district sanitaire d'Adzopé : cas des localités d'Asseudji

Abstract: This article reports on a cross-sectional study which aims to describe the situation of yaws in the boroughs of Asseudji located in the health district of Adzopé. The study's population group consisted of 206 household heads, and 2182 subjects who were tested and examined for yaws. The primary sources of pollution levels for a household were domestic animal waste (100%) and garbage stored in close proximity to the household's dwelling (49%). Signs of over-crowding were found in 43.7% of households. The sore "m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Our systematic review identified 103 records, from which we identified 23 eligible published articles 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 that described 27 studies that met our inclusion criteria ( figure 1 ). We included data from an additional four studies identified from other sources (personal communications with country managers and yaws experts: Tabah EN, personal communication; Boua B, personal communication; Nsiire A, personal communication; Ayelo G, personal communication).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our systematic review identified 103 records, from which we identified 23 eligible published articles 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 that described 27 studies that met our inclusion criteria ( figure 1 ). We included data from an additional four studies identified from other sources (personal communications with country managers and yaws experts: Tabah EN, personal communication; Boua B, personal communication; Nsiire A, personal communication; Ayelo G, personal communication).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 31 studies, 16 reported data on active yaws prevalence ( table 1 ; Tabah EN, personal communication; Boua B, personal communication; Nsiire A, personal communication). 9 , 10 , 13 , 14 , 16 , 18 , 19 , 20 , 21 , 24 , 28 , 29 , 30 Patients with suspected yaws skin lesions were further tested with syphilis serology, except in four studies in which diagnosis was made on the basis of clinical criteria only (Tabah EN, personal communication; Boua B, personal communication). 16 , 19 After excluding one study from Ecuador 29 in 1998 in which no clinical cases were detected, prevalence of active yaws lesions ranged from 0·31% in Sumatra, Indonesia, 18 to 14·54% around the city of Port Moresby, Papua New Guinea.…”
Section: Resultsmentioning
confidence: 99%